Environment, archaeology and landscape : papers in honour of Professor Martin Bell - Bell, Martin, 1953-; Barnett, Catherine; Walker, Thomas (Archaeopress Archaeology, 2021)
'Environment, Archaeology and Landscape' is a collection of papers dedicated to Martin Bell on his retirement as Professor of Archaeological Science at the University of Reading. Three themes outline how wetland and inland environments can be related and investigated using multi-method approaches.